KEEFEKTIFAN TEKNIK SYMBOLIC MODELING UNTUK MENINGKATKAN MOTIVASI BERPRESTASI PESERTA DIDIK SMP - Fauziah, Riza; Fadhilah, Siti Sutarmi; Djannah, Wardatul (Consilium: Jurnal Program Studi Bimbingan dan Konseling, 2017)
This research purposes to determine the effectiveness of group guidance with symbolic modeling technique for improved students achievement motivation. This research using quasi experimental non equivalent control group design with the middle high school student who have low achivement motivation as research subject. The achievement Motivation level is determained with achievement motivation quitionnaire was validated using product moment test and for reliability test using Alpha- Cronbach test. The Test results showed that group guidance with symbolic modeling technique effective for improved students achievement motivation.